2010
DOI: 10.1590/s0104-11692010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Profile and severity of the patients of intensive care units: prospective application of the APACHE II index

Abstract: This study aimed to understand the profile and severity of patients in physiotherapy treatment after their admission to the intensive care unit (ICU) by applying the APACHE II index. One hundred and forty six subjects, with a mean age of 60.5 ± 19.2 years, were evaluated. The APACHE II index was applied in the first 24 hours to evaluate the severity and mortality risk score. Patients were monitored until hospital discharge or death. The mean APACHE II score was 20±7.3 with an estimated risk of death of 32.4% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
(16 reference statements)
3
14
0
8
Order By: Relevance
“…(5,13) One of the reasons that may justify this result is the lack of a semi-intensive unit in the hospital assessed, which means that less critical patients are admitted in the ICU. However, the most severe patients assessed by APACHE II experienced more AE, a similar result to the ones found in national literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5,13) One of the reasons that may justify this result is the lack of a semi-intensive unit in the hospital assessed, which means that less critical patients are admitted in the ICU. However, the most severe patients assessed by APACHE II experienced more AE, a similar result to the ones found in national literature.…”
Section: Discussionmentioning
confidence: 99%
“…One of them is the prognostic index Acute Physiology and Chronic Health Evaluation II (APACHE II), developed to estimate severity of disease and predict hospital mortality. (5) Another instrument is the Nursing Activities Score (NAS), which measures the nursing workload including direct care actions, family support and management activities. (6) NAS monitoring allows determining the nursing team staffing in order to provide the necessary care.…”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence of complications resulting from deleterious effects of immobility in Intensive Care Units (ICUs) is related to the decline of functional independence, excessive welfare costs, decreased quality of life, and post-discharge survival 1 .…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted at the intensive care unit of a nonprofit hospital in the state of Paraná assessed patient severity by means of the APACHE II score .The results showed that patients over the age of 60 years were more likely to have comorbidities. (13) A study conducted at the intensive care unit of a university hospital in São Paulo assessed differences in nursing workload (NAS) and severity (SAPS II) among elderly and non-elderly patients. The authors found that nursing workload was no different among elderly patients of different age ranges, but patients aged 80 or older had the highest severity indices (66.7%).…”
Section: Discussionmentioning
confidence: 99%